[LCu]_2biPy/GC电极L-半胱氨酸的伏安测定 - 王明艳; 杨凡; 张圣玉; 许兴友; 杨绪杰; WANG Ming-yan; YANG Fan; ZHANG Sheng-yu; XU Xing-you; YANG Xu-jie (厦门大学《电化学》编辑部, 2008)
[LCu]2b iPy/GC电极对L-半胱氨酸(L-Cys)具有良好的电催化氧化作用,催化电流(Ipa)与L-Cys浓度(C)在1×10-3到300 mmol.L-1范围内呈线性关系,相关系数0.9996,检出下限达5×10-7mol.L-1. A modified electrode has been constructed by depositing a novel copper(Ⅱ) complex 2biPy(ClO4)4 on the glassy carbon electrode through the method of cyclic voltammetry(CV).It was found that the modified electrode exhibited high electrocatalytic activity toward L-Cysteine oxidation with good reproducibility and high sensitivity.The peak current of semi-derivative linear scan was proportional to the concentration of L-cys in the range of 1×10-6～3×10-4 mol·L-1.The detection limit was 5×10-7 mol·L-1. 作者联系地址：淮海工学院化学工程学院;南京理工大学材料化学实验室; Author's Address: 1.School of Chemical Engineering,Huaihai Institute of Technology,Lianyungang 222005,Jiangsu,China;2.Laboratory of Materials Chemistry,Nanjing University of Science and Technology,Nanjing 210094,China